2010
DOI: 10.1111/j.1524-4725.2010.01703.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial Rejuvenation After Intradermal Botulinum Toxin: Is it Really the Botulinum Toxin or is it the Pricks?

Abstract: Intradermal botulinum toxin A injection does not appear to have any benefit in facial rejuvenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 8 publications
0
50
0
Order By: Relevance
“…9 As this procedure could be performed by injecting multiple tiny aliquots of a more diluted concentration of BTA than traditional dilution into dermis, the collagen production found after treatment may probably cause by needle pricks, not BTA itself. 10 In addition, few split-face comparison studies on OnabotulinumtoxinA (ONA) demonstrated no clinical efficacy on face-lifting effect when comparing to normal saline solution (NSS) using intradermal injection technique. 9,10 To the best of our knowledge, this was the first study to compare the face-lifting effect of ABO intradermal injection and NSS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 As this procedure could be performed by injecting multiple tiny aliquots of a more diluted concentration of BTA than traditional dilution into dermis, the collagen production found after treatment may probably cause by needle pricks, not BTA itself. 10 In addition, few split-face comparison studies on OnabotulinumtoxinA (ONA) demonstrated no clinical efficacy on face-lifting effect when comparing to normal saline solution (NSS) using intradermal injection technique. 9,10 To the best of our knowledge, this was the first study to compare the face-lifting effect of ABO intradermal injection and NSS.…”
Section: Discussionmentioning
confidence: 99%
“…10 In addition, few split-face comparison studies on OnabotulinumtoxinA (ONA) demonstrated no clinical efficacy on face-lifting effect when comparing to normal saline solution (NSS) using intradermal injection technique. 9,10 To the best of our knowledge, this was the first study to compare the face-lifting effect of ABO intradermal injection and NSS. Even though, we found that there was a statistically significant difference in face-lifting effect when comparing between ABO and NSS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One may reasonably suspect that an effect might be produced on adjacent tissue components after BoNT injection, but what makes this argument even more interesting is that percutaneous needle pricks themselves have been reported to create multiple microbruises in the dermis and to initiate a complex cascade of growth factors that eventually results in collagen production. Thus, intradermal BoNT injection might not have any benefit for facial rejuvenation, the purported benefits of skin rejuvenation being due to the collagenesis caused by the needle pricks . Therefore, studies of BoNT effects on collagenesis of human dermal fibroblasts in vitro that exclude the effects of needles must be designed.…”
Section: Discussionmentioning
confidence: 99%
“…46 They considered it debatable whether the postulated effects are truly due to an intradermal mechanism of action or to the spread of botulinum toxin to underlying and adjacent muscles. From an evidence-based perspective, large, placebo-controlled trials would be required to evaluate the efficacy of intradermal botulinum toxin injection.…”
Section: Position Statementsmentioning
confidence: 99%